1988
DOI: 10.1063/1.454345
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and torsional motion of biphenyl in the ground and first excited singlet state

Abstract: The lowest excited singlet state of biphenyl (BP) and a number of its isotopically and chemically substituted analogs have been studied by supersonic jet laser spectroscopy. The symmetry species of this excited state in BP can be classified as B 2-:; in the G I6 extended molecular symmetry group G I6 (EM). The symmetry-allowed origin of the biphenyl-h SI +-So electronic transition occurs at 35 268 cm-I. The frequency ofthe torsional moti~n in S is determined to be-65 cm-I. The potential parameters for this mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 32 publications
(1 reference statement)
6
71
2
2
Order By: Relevance
“…[24] Relatively intense fluorescence is apparent in fluid solution and is centred around 340 nm ( Figure 2); the spectral profile and peak position are insensitive to changes in excitation wavelength. The excitation spectrum matches closely with the absorption profile for each polyether while the fluorescence and absorption bands show reasonable mirror [27] Fluorescence quantum yields (Φ F ) are about 0.10 and only slightly dependent on the length of the polyether strap (Table 1). Fluorescence decay profiles were strictly monoexponential regardless of monitoring wavelength and unaffected by the presence of dissolved molecular oxygen.…”
Section: Photophysical Studiesmentioning
confidence: 56%
“…[24] Relatively intense fluorescence is apparent in fluid solution and is centred around 340 nm ( Figure 2); the spectral profile and peak position are insensitive to changes in excitation wavelength. The excitation spectrum matches closely with the absorption profile for each polyether while the fluorescence and absorption bands show reasonable mirror [27] Fluorescence quantum yields (Φ F ) are about 0.10 and only slightly dependent on the length of the polyether strap (Table 1). Fluorescence decay profiles were strictly monoexponential regardless of monitoring wavelength and unaffected by the presence of dissolved molecular oxygen.…”
Section: Photophysical Studiesmentioning
confidence: 56%
“…For B-type molecules (e.g., nPVs and long nTs (n ≥ 3)), the equilibrium geometry is planar in both the S 0 and S 1 states when T → 0 K, and yields a mirror symmetry. In C-type molecules (e.g., nPs) the equilibrium geometry is nonplanar in the ground state, [19][20][21] and there is no mirror symmetry between the absorption and emission, regardless of the temperature (Fig. 3c).…”
Section: Experimental Determination Of the S 0 -S 1 Transition Energymentioning
confidence: 96%
“…[15][16][17] Furthermore this type of unit has been considered as a potential conductance switch as the two p systems can be either in the same plane or perpendicular to each other representing the "on" and "off" states of a molecular switch, respectively. [18][19][20] In a recent study, Venkataraman [10] and co-workers reported the interdependence between the calculated molecular conformation and the single-molecule conductance of a series of various substituted biphenyls having terminal amino groups.…”
Section: Dedication To Professor Hans Kuhn On the Occasion Of His 90tmentioning
confidence: 99%